Air–Water Jet Wiper System for Continuous Visibility and Driver Safety - Ananthan, Sharveswaran; Mohammad, Roslina; Maarop, Nurazean; Sarip, Shamsul; Hassan, Mohamad Zaki; Suhot, Mohamed Azlan; Bastuti, Sofian; Alfatiyah, Rini (Journal of Advanced Research Design, 2025)
Ensuring continuous driver visibility during rainfall remains a persistent challenge, as conventional blade-based systems cause intermittent vision loss, uneven coverage, and high maintenance requirements. This study proposes and validates a bladeless smart wiper washing system that integrates synchronized micro-jet water spraying with high-pressure air-jet drying to eliminate temporary blindness and enhance safety. The system was conceptualized using CAD modeling, structurally validated via finite element analysis (von Mises stress), and fabricated into a working prototype consisting of a hollow aluminum rod with twenty-one 1 mm micro-nozzles, a 12 V pump, a compressor, and a synchronized control unit. Experimental testing demonstrated more than 85% uniform spray coverage, rapid cleaning cycles of 2–4 s compared to 5–10 s for conventional wipers, reduced fluid consumption (~100 mL per cycle versus 200–300 mL), and markedly lower operational noise. Comparative evaluations confirmed that the bladeless configuration eliminated blade streaking, minimized mechanical wear, and provided uninterrupted visibility even under simulated rainfall. Structural simulations were consistent with prototype behavior, indicating robust performance within the tested pressure range. Collectively, the findings establish that integrating micro-jet spraying with air-jet clearing offers a viable pathway toward safer, quieter, and more resource-efficient windshield cleaning. The approach is particularly suited for next-generation vehicles and ADAS platforms where continuous visibility is essential. Future research will focus on adaptive sensing and closed-loop control strategies to optimize jet activation under real-world environmental conditions.